2015
DOI: 10.1159/000371554
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of a Glucose-Sparing PD Therapy on Glycemic Control Measured by Serum Fructosamine in Diabetic Patients in a Randomized, Controlled Trial (IMPENDIA)

Abstract: Background/Aims: Poor glycemic control can lead to increased morbidity and mortality in peritoneal dialysis (PD) patients. Serum fructosamine may be a more reliable marker of glycemic control than HbA1c in dialysis patients. Methods: We evaluated the effects of a glucose-sparing PD regimen on serum fructosamine. In the multicenter, controlled IMPENDIA trial, eligible diabetic PD patients were randomized (1:1) to a 24-hour combination of a glucose sparing regimen (n = 89) or a glucose-based therapy (n = 91). Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…86,127 However, our analysis showed no difference in HbA 1c and fasting plasma glucose levels between groups. Given results of the IMPENDIA-EDEN trial, 128,129 a single exchange of icodextrin per day instead of glucose may be clinically insufficient as a glucose-sparing PD regimen. Alternatively, the effect may be too small to be demonstrable in our data set, which includes many nondiabetic patients (a "sub-metaanalysis" of the effect of icodextrin-containing PD regimens on glycemic control exclusively in diabetic patients is underway).…”
Section: Discussionmentioning
confidence: 99%
“…86,127 However, our analysis showed no difference in HbA 1c and fasting plasma glucose levels between groups. Given results of the IMPENDIA-EDEN trial, 128,129 a single exchange of icodextrin per day instead of glucose may be clinically insufficient as a glucose-sparing PD regimen. Alternatively, the effect may be too small to be demonstrable in our data set, which includes many nondiabetic patients (a "sub-metaanalysis" of the effect of icodextrin-containing PD regimens on glycemic control exclusively in diabetic patients is underway).…”
Section: Discussionmentioning
confidence: 99%
“…G lucose is the most common osmotic medium used in peritoneal dialysis (PD) solutions and is used in varying concentrations (75.5 to 214 mmol/L) to induce ultrafiltration (1,2). Glucose in PD solutions is absorbed and contributes to a number of potential systemic adverse effects, including poor glycemic control, weight gain, dyslipidemia, and increased cardiovascular risk (3 4 5 6 7 8 9-10). Furthermore, the glucose in PD solutions causes damaging local membrane effects, such as membrane thickening and vasculopathy, and immunological effects, such as stimulated inflammatory cytokine secretion and impaired phagocytosis (11,12), perhaps through the effects of advanced glycosylated end-product (AGE) formation and direct cytotoxicity of glucose degradation products (GDPs) on the peritoneum (3,1320).…”
mentioning
confidence: 99%
“…Results and conclusions from the combined (IMPENDIA/EDEN) trials (The Improved Metabolic Control of Physioneal, Extraneal, Nutrineal (P-E-N) versus Dianeal Only in DIAbetic continuous ambulatory peritoneal dialysis (CAPD) and automated peritoneal dialysis (APD) Patients (IMPENDIA), and The Evaluation of Dianeal, Extraneal, Nutrineal (D-E-N) versus Dianeal only in Diabetic CAPD Patients (EDEN)) showed that a low-glucose PD regime improves metabolic indexes in diabetic patients receiving peritoneal dialysis, but may be associated with an increased risk of extracellular fluid volume expansion. Thus, the use of glucose-sparing regimens in peritoneal dialysis patients should be accompanied by close monitoring of fluid volume status [ 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there has been a considerable interest in minimizing the use of dextrose exposure during PD. The peritoneal dialysis solutions used in combination have reduced the complications and allows a long-time function of the peritoneal membrane, as they also can contribute to reducing the cardiovascular risk of PD patients [ 7 , 8 , 9 ]. On the other-hand, preservation of residual renal function (RRF) in patients on PD is crucial for the maintenance of life quality and long-term survival [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%